Cap Assisted Upper Endoscopy for Examination of the Major Duodenal Papilla: A Randomized, Blinded, Controlled Crossover Study (CAPPA Study). (May 2017) - Abdelhafez, Mohamed; Phillip, Veit; Hapfelmeier, Alexander; Elnegouly, Mayada; Poszler, Alexander; Strobel, Kilian; Born, Peter; Dollhopf, Markus; Kassem, Abdel Meguid; Calavrezos, Lenika; Klare, Peter; Schlag, Christoph; et al.
Abstract : Objective: Examination of major duodenal papilla (MDP) by standard forward‐viewing esophagogastroduodenoscopy (S‐EGD) is limited. Cap assisted esophagogastroduodenoscopy (CA‐EGD) utilizes a cap fitted to the tip of the endoscope that can depress the mucosal folds and thus might improve visualization of MDP. The aim of this study was to compare CA‐EGD to S‐EGD for complete examination of the MDP. Methods: Prospective, randomized, blinded, controlled crossover study. Subjects scheduled for elective EGD were randomized to undergo S‐EGD (group A) or CA‐EGD (group B) before undergoing a second examination by the alternate method. Images of the MDP were evaluated by three blinded multicenter‐experts. Our primary outcome measure was complete examination of the papilla. Secondary outcome measures were duration and overall diagnostic yield. Results: A total of 101 patients were randomized and completed the study. Complete examination of MDP was achieved in 98 patients using CA‐EGD compared to 24 patients using S‐EGD (97 vs. 24%, P <0.001). Median duration from intubation of the esophagus until localization of the MDP was shorter with CA‐EGD (46. vs. 96 s., P <0.001). In group A, 11 extra lesions and 12 additional incidental findings were detected by secondary CA‐EGD, whereas neither were detected by secondary S‐EGD in group B (22 vs. 0% and 24 vs. 0%, P <0.001 and P <0.001). Conclusion: CA‐EGD enabled complete examination of MDP in almost all cases compared to a low success rate of S‐EGD. CA‐EGD detected a significant amount of lesions and incidental findings when added to S‐EGD. CA‐EGD is a safe and effective method for examination of MDP.